Avenanthramide supplementation reduces eccentric exercise-induced inflammation in young men and women. Issue 1 (25th July 2020) - Zhang, Tianou; Zhao, Tong; Zhang, Yuzi; Liu, Tao; Gagnon, Gilles; Ebrahim, Jacqueline; Johnson, Jodee; Chu, Yi-Fang; Ji, Li Li
Abstract: Background: Avenanthramides (AVA) are a group of di-phenolic acids found only in oats and have shown antioxidant and anti-inflammatory effects in vitro and in vivo. Eccentric muscle contraction is intimately involved in rigorous exercise that activates systemic and local inflammatory responses. The objective of the study is to evaluate whether chronic AVA supplementation could attenuate peripheral inflammatory and immunological markers in human subjects in response to an acute bout of downhill running (DR). Methods: Eleven male and thirteen female subjects voluntarily participated in this double-blinded, randomized controlled study and were randomly divided into AVA-supplemented (AVA) or control (C) groups. All subjects conducted a DR protocol at − 10% grade with an intensity equivalent to 75% of their maximal heart rate. Blood samples were collected at rest and various time points (0-72 h) after DR (PRE). After an 8-week washout period, participants received two cookies daily containing either 206 mg/kg (AVA) or 0 mg/kg (C) AVA for 8 weeks. Following the oat supplementation regimen, the DR and blood sampling protocols were repeated (POST). Plasma inflammatory and immunological markers were measured using Multiplex immunoassay and muscle soreness was evaluated with pain rating scale. Results: DR increased plasma creatine kinase (CK) activity ( P  < 0.01) during PRE, but the response was reduced at 24 and 48 h during POST vs. PRE regardless of AVA status ( P  < 0.05). Neutrophil respiratory burst (NRB) levels were elevated at 4 and 24 h ( P  < 0.05) during PRE but were significantly decreased at 0–48 h during POST vs. PRE ( P  < 0.05 or 0.01). Granulocyte-colony stimulating factor (G-CSF), the neutrophil stimulating cytokine, was also increased in response to DR but showed lower levels in AVA compared to C during POST vs. PRE ( P  < 0.05). Plasma interleukin-6 (IL-6) content showed an increase at 0 and 4 h during PRE and 0 h during POST ( P  < 0.01), whereas during POST there was a trend toward a lower IL-6 level in AVA vs. C ( P  = 0.082). Plasma levels of anti-inflammatory agent interleukin-1 receptor antagonist (IL-1Ra) showed an increase at 4 h during PRE, and was significantly elevated in AVA vs. C during POST. Both soluble vascular cell adhesion molecule-1 (sVCAM-1) and monocyte chemoattractant protein-1 (MCP-1) contents increased at 0 and 24 h post DR during PRE as well as POST sessions, however, sVCAM-1 content was lower in AVA vs. C during POST ( P  < 0.05) and MCP-1 levels were below resting level at 24, 48 and 72 h during POST ( P  < 0.05). DR increased muscle pain at all post-DR time points ( P  < 0.01), but the pain level was alleviated by oat supplementation at 48 and 72 h during POST regardless of AVA treatment ( P  < 0.05). Conclusions: Oat AVA supplementation reduced circulatory inflammatory cytokines and inhibited expression of chemokines and cell adhesion molecules induced by DR. Trial registration: ClinicalTrials.gov identifier: NCT02584946 . Registered 23 October 2015.